PERILAKU SEKSUAL LESBIAN TERKAIT PERSONAL HYGIENE DI KOTA BANDUNG - Liwanti Subagio; Emmy Riyanti; Syamsulhuda BM (Jurnal Kesehatan Masyarakat (Undip), 2017)
Lesbians are the same-sex oriented enthusiasts between women and women. Its presence in Indonesia continues to grow especially in big cities, one of which is the city of Bandung is famous as the Metropolitan City. In the city of Bandung lesbi already dare to show off in public places even dare to conduct sexual behavior in public places. Lesbian sexual behavior can adversely affect health such as cervical cancer, hepatitis, sexually transmitted infections, to HIV / AIDS. One of the causes is personal hygiene. Personal hygiene is an act to maintain a person's hygiene and health. This qualitative descriptive research collected data by in-depth interview to 7 respondents with snowball method. Processing and data analysis of validity and reliability with triangulation. Respondents interviewed had an age range of 19 - 25 years. Latest education from all respondents high school and bachelor. Background of the respondent to a lesbian is broken home, hurt due to men, the environment and begins with a trial and error. Recognized label respondents there are four types namely no labeling, femme, andro, and butch. The results of research on lesbian sexual behavior related to personal hygiene performed by all respondents in the form of sexual behavior that he did was oral, fingering, liking, scissoring, and using dildos. Respondents are not afraid to engage in sexual behavior because they have a good knowledge of personal hygiene. The practice is to wash your hands with liquid soap and stem, not to let your nails grow long, keep your mouth clean by rinsing with mouthwash and toothbrush, and take a bath as a way to keep the overall cleanliness.